Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2012
DOI: 10.1063/1.4746028
|View full text |Cite
|
Sign up to set email alerts
|

Top electrode size effect on hysteresis loops in piezoresponse force microscopy of Pb(Zr,Ti)O3-film on silicon structures

Abstract: Experimental and theoretical studies of hysteresis loops in piezoresponse force microscopy (PFM) directed on elucidating the influence of top electrode lateral sizes on loop peculiarities were performed for Pt/Pb(Zr, Ti)O 3 /Pt/TiO x /SiO 2 /Si-substrate structures. The set of top Pt electrodes (50 nm to 10 lm of lateral size) was deposited on the Pb(Zr x Ti 1Àx )O 3 film (x ¼ 0.54, thickness %1 lm) by RF magnetron sputtering. Under approaching the top electrode lateral size to the film thickness, the transiti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
3
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 38 publications
3
3
0
Order By: Relevance
“…The electric charge is dramatically increased while the effective piezoelectric coefficient is greatly suppressed and they both transfer from the HS solutions to the IT results when / a t varies from 0.001 to 20. And a transition-like behavior between the HS and IT cases is also observed at about / a t=1 as reported in the experimental research of Bravina et al [13]. Then a critical top electrode size, i.e., > / a t 10, is obtained and applicable to other piezoelectric materials.…”
Section: Discussionsupporting
confidence: 72%
See 2 more Smart Citations
“…The electric charge is dramatically increased while the effective piezoelectric coefficient is greatly suppressed and they both transfer from the HS solutions to the IT results when / a t varies from 0.001 to 20. And a transition-like behavior between the HS and IT cases is also observed at about / a t=1 as reported in the experimental research of Bravina et al [13]. Then a critical top electrode size, i.e., > / a t 10, is obtained and applicable to other piezoelectric materials.…”
Section: Discussionsupporting
confidence: 72%
“…And for large electrode size, e.g., 1.2 μm, the effective piezoelectric coefficient decreases to a constant. This size effect and transition-like behavior have also been reported by Bravina et al [13] investigating the piezoresponses of PZT films with different top electrode radii. Wang et al [16] studied the electrode size effects using finite element analysis and found that for pads less than a few mm the displacement of the top surface is greatly reduced.…”
Section: Introductionsupporting
confidence: 82%
See 1 more Smart Citation
“…It is noteworthy that recent phenomenology and first-principle calculations have demonstrated that asymmetric electrodes could lead to distinguished ferroelectric size effect, imprint behaviors, and novel properties (e.g., dielectric behavior and electron transport) in ferroelectric thin films from their symmetric counterparts, such as smearing of the phase transition, an induced piezoelectric response above T c , and reversal of the polarization asymmetry by application of biaxial strain etc. , which should be further verified experimentally (e.g., via x-ray diffraction analysis) [ 252 , 299 , 308 , 309 , 310 , 311 , 312 , 313 ]. To be more clear, we would like to take the theoretical research of Zheng et al [ 311 ] as an example, where asymmetric ferroelectric capacitors (A-FCs) with a single-domain ferroelectric thin film (FTF) sandwiched between different electrodes has been investigated ( Figure 9 a).…”
Section: Important Phenomena In Ferroelectric Thin Filmsmentioning
confidence: 99%
“…54 A number of authors investigate the image formation mechanism in PFM. The size effect on PFM is studied by Bravina et al, 55 continuing a series of detailed work on mathematical underpinning of PFM signal under various conditions. Reconstruction of domain structures from PFM data is nicely elaborated by Li et al 56 Finally, the significant effort is devoted to the role of surface electrochemical processes on polarization dynamics as determined by PFM.…”
mentioning
confidence: 99%